Postload hyperglycemia is associated with increased subclinical inflammation in patients with prediabetes. (August 2013) - Colak, Ayfer; Akinci, Baris; Diniz, Gulden; Turkon, Hakan; Ergonen, Faruk; Yalcin, Hulya; Coker, Isil
Abstract Background/aims. In this present study, we aimed: (i) To clarify if prediabetes is associated with subclinical inflammation independent of underlying obesity, and (ii) to evaluate the effect of postload glucose concentration on subclinical inflammation markers in a group of patients with elevated fasting glucose. Material and methods. In a cohort of 165 patients with newly detected fasting hyperglycemia, according to 75 g oral glucose tolerance test (OGTT), subjects were classified either as newly diagnosed type 2 diabetes (diabetes group, n = 40), impaired fasting glucose (IFG) plus impaired glucose tolerance (IGT) (IFG/IGT group, n = 42) or IFG only (IFG group, n = 83). A control group (n = 47) consisted of age- and body mass index (BMI)-matched healthy subjects with a normal OGTT. Circulating concentrations of lipids, insulin, interleukin-6 (IL-6), interleukin-8 (IL-8) and high sensitive C-reactive protein (hsCRP) were measured. HOMA index was calculated. Results. Subclinical inflammation markers were elevated in patients with diabetes and IFG/IGT compared to healthy controls and also IFG patients (diabetes vs. control: p < 0.05 for hsCRP, IL-8, and IL-6; IFG/IGT vs. control: p < 0.05 for hsCRP, and IL-6; diabetes vs. IFG: p < 0.05 for hsCRP, and IL-6; IFG/IGT vs. IFG: p < 0.05 for hsCRP, and IL-6). In multiple regression analysis, postload glucose concentration was independently associated with circulating hsCRP and IL-6 concentrations when the data was controlled for age, gender, BMI and lipid concentrations (p < 0.05 for hsCRP, and IL-6). Conclusion. Our results suggest that patients with prediabetes, independent of underlying obesity, have increased concentrations of subclinical inflammation which is mostly driven by postload glucose concentrations.